2017
DOI: 10.1016/j.plaphy.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of metal oxide nanoparticles with higher terrestrial plants: Physiological and biochemical aspects

Abstract: Multiple applications of metal oxide nanoparticles (MONPs) could result in their accumulation in soil, threatening higher terrestrial plants. Several reports have shown the effects of MONPs on plants. In this review, we analyze the most recent reports about the physiological and biochemical responses of plants to stress imposed by MONPs. Findings demonstrate that MONPs may be taken up and accumulated in plant tissues causing adverse or beneficial effects on seed germination, seedling elongation, photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(122 citation statements)
references
References 120 publications
4
108
0
4
Order By: Relevance
“…(Larue et al, 2012), Hordeum vulgare (Mattiello et al, 2015), and Zea mays (Morteza et al, 2013). The range of toxic effects include inhibition of seed germination, seedling elongation, photosynthetic efficiency of shoot, generation of ROS, cytotoxicity and genotoxicity (Cox et al, 2016; Du et al, 2017). Genome-wide expression analysis of the effect of nanoparticles including TiO 2 has shown that the root hair development and antistress defense responses are significantly affected in Arabidopsis (Garcia-Sanchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Larue et al, 2012), Hordeum vulgare (Mattiello et al, 2015), and Zea mays (Morteza et al, 2013). The range of toxic effects include inhibition of seed germination, seedling elongation, photosynthetic efficiency of shoot, generation of ROS, cytotoxicity and genotoxicity (Cox et al, 2016; Du et al, 2017). Genome-wide expression analysis of the effect of nanoparticles including TiO 2 has shown that the root hair development and antistress defense responses are significantly affected in Arabidopsis (Garcia-Sanchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this stage, the impact mechanism is important to determine the complex effects of nanoparticles such as composition, surface charge, physicochemical properties in shape and size. Some of these properties can be toxic to living organisms . Release of nanoparticles into the environment can occur naturally, accidentally (such as, from industrial process) or deliberately (such as, from pesticides or fertilizers).…”
Section: Introductionmentioning
confidence: 99%
“…Plants can uptake and translocate the metal oxide nanoparticles via root (through the apoplastic and symplastic pathway) or leaf (through the stomata or cuticle and then through the phloem) pathways . There are several studies showing that metal oxide nanoparticles had adverse effects (physiological, antioxidant activities, and photosynthetic) in plants . These studies showed that different nanoparticles have different impact in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect human health and plant from the prospective antagonistic effects of a wide range of nanomaterials, an increasing number of research have focused on the assessment of the toxicity of the NPs normally used in industry (Yang and Watts, 2005; Rana and Kalaichelvan, 2013; Du et al, 2017; Tripathi et al, 2017a,b,c). The toxicity of a metal depends upon several factors like solubility, binding specificity to a biological site, and so forth.…”
Section: Nanotechnology and Agricultural Sustainable Developmentmentioning
confidence: 99%
“…NPs in plants enter cellular system, translocate them shoot and accumulate in various aerial parts, the possibility of their cycling in the ecosystem increases through various trophic levels. After accumulation of NPs effect rate of transpiration, respiration, altering the process of photosynthesis, and interfere with translocation of food material (Shweta et al, 2016; Tripathi et al, 2016b; Du et al, 2017). The degree of toxicity is linked to this surface and to the surface properties of the NPs.…”
Section: Nanotechnology and Agricultural Sustainable Developmentmentioning
confidence: 99%